METODE PAPAN CATUR PADA PEKERJAAN PELINDUNG BANTARAN DI SUNGAI BENGAWAN SOLO - , RYAN KAMESWARA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Generaly strengthening of slopes (Revetment) is a building that is placed on a slope that serves to protect a coastal cliff or slope surface flow and as a whole served to increase the stability of the river channel or levee that protected the body. In particular, the beach or revetment walls can also be defined as a building that separates land and water, which primarily serves as a protective wall against erosion of riverbanks and wave overtopping ashore. Protected land area is right behind the building. The surface of the building facing the direction of the waves can be either vertical or sloping sides. The walls are usually shaped beach while the vertical wall reinforcement slope (revetment) have sloping sides. Method of Revetment on flood plains solo riverbank using the chessboard pattern is done using intermitent method, is considered very efiesien workmanship as is done on both sides of the river, so as to speed up the work, to carry out the same thing on his workmanship revetment to revetment construction other there excavations, covering/dewatering, leveling concrete, formwork, Reinforcement and final casting in this project there are also concrete care to protect the concrete from extreme weather. The results of the analysis of the carrying capacity calculations revetment stability obtained under normal conditions to the turning of FGL 7610 greater than 1.50, Stability of the shearing of FGS = 5365 greater than 1.5 and the final collapse of the Stability of the soil bearing capacity of 4,192 t/m2 greater than 10.0 t/m2 the seawall could withstand the force under normal conditions